2010
DOI: 10.17221/142/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life extension of liquid whole eggs by heat and bacteriocin treatment

Abstract: During a 15-month period, samples of commercially pasteurised liquid whole egg (LWE) were tested for the presence of spoilage microflora. The total bacterial counts were 2.2 ± 0.6 log CFU/g and total lactic acid bacteria (LAB) counts were 1.9 ± 0.6 log CFU/g. Enterobacteriaceae were detected in 2 samples. Out of the tested samples, 45 LAB were isolated and identified, with 30 strains identified as Enterococcus faecium, 12 as Enterococcus faecalis, and 3 as Lactobacillus paracasei subsp. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
(25 reference statements)
5
15
0
Order By: Relevance
“…However, the 4 Enterococcus faecalis isolates were highly proteolytic. Although performed under different conditions regarding the type (liquid or dried milk, casein) and concentration of the substrates, the type of culture (liquid or solid), and the type of detection of the activity (spectrophotometry for liquid cultures), the data presented in the present study confirmed those of Veljovic and others (), Miller and others (), and Moreno and others (). These authors have reported that the level of the proteolytic activity depended on the strain inside a same genus.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…However, the 4 Enterococcus faecalis isolates were highly proteolytic. Although performed under different conditions regarding the type (liquid or dried milk, casein) and concentration of the substrates, the type of culture (liquid or solid), and the type of detection of the activity (spectrophotometry for liquid cultures), the data presented in the present study confirmed those of Veljovic and others (), Miller and others (), and Moreno and others (). These authors have reported that the level of the proteolytic activity depended on the strain inside a same genus.…”
Section: Resultssupporting
confidence: 89%
“…Finally, the remaining of enterococci concerned 93% of the contaminated pasteurized liquid egg white samples analyzed, corroborating the observations of Protais and others (), Hidalgo and others (), and Miller and others () in whole egg products. Enterococci are widely distributed in the environment, principally inhabiting the human and animal gastrointestinal tract (Moreno and others for review).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The surviving bacteria are gram-positive cells of the genera Streptococcus, Enterococcus and, as expected, the sporeforming Bacillus. With the exception of (Miller et al, 2010), who discussed the expression of proteolytic and lipolytic activities by Enterococcus spp. Strains isolated from whole egg products, the involvement of bacterial enzymatic activities in the spoilage of egg products has not received sufficient attention for establishing a clear relationship between a type of bacterium and a specific characteristic of spoilage.…”
Section: Spoilage Of Egg Productsmentioning
confidence: 99%